Open-Label, Randomized, Two-Way, Crossover Study Assessing the Bioequivalence of the Liquid Formulation versus the Freeze-Dried Formulation of Recombinant Human FSH and Recombinant Human LH in a Fixed 2:1 Combination (Pergoveris®) in Pituitary-Suppressed Healthy Women - Bagchus, Wilhelmina; Yalkinoglu, Özkan; Wolna, Peter (Frontiers in Endocrinology, 2018)
This was a Phase I, open-label, randomized, two-period, two-sequence crossover study (ClinicalTrials.gov NCT02317809 [https://www.clinicaltrials.gov/ct2/show/NCT02317809]; EudraCT 2014-003506-32) assessing the bioequivalence of the liquid and freeze-dried formulations of fixed-dose, fixed-ratio (2:1) combination recombinant-human follicle-stimulating hormone plus recombinant-human luteinizing hormone (r-hFSH/r-hLH). The safety and tolerability of the two formulations were also assessed. Healthy premenopausal women were randomized to one of two crossover dosing schedules. Subjects in Treatment Sequence 1 received a single subcutaneous dose (900/450 IU r-hFSH/r-hLH) of the liquid formulation of r-hFSH/r-hLH on Day 1 of Dose Period 1 and, after a wash-out period of at least 14 days, a single subcutaneous dose (900/450 IU r-hFSH/r-hLH) of the freeze-dried formulation of r-hFSH/r-hLH (reconstituted in water for injection prior to administration) on Day 1 of Dose Period 2. Subjects in Treatment Sequence 2 received the treatments in reverse order. The primary endpoints were AUC0–t (area under the serum concentration–time curve from time 0 to the time of the last quantifiable concentration) and Cmax (maximum serum concentration) for FSH and LH, both baseline corrected. A total of 34 subjects were randomized and 22 subjects were included in the bioequivalence evaluation. Overall, the mean observed PK profiles and individual PK parameters were comparable for the liquid and freeze-dried formulations, although a median difference in the tmax (time to reach maximum observed concentration) of FSH of 4.5 hours was observed between the formulations. The calculated 90% confidence intervals of the mean liquid-formulation/freeze-dried-formulation ratios for Cmax and AUC0–t were within the bioequivalence range (80−125%) for both LH and FSH, confirming bioequivalence between the two formulations. The safety and tolerability profiles of the two formulations were similar. The liquid formulation can therefore be expected to provide the same efficacy as the freeze-dried formulation, with no differences in tolerability.